Development and optimization of gastroretentive mucoadhesive microspheres of gabapentin by Box–Behnken design. (June 2014) - Gaur, Praveen Kumar; Mishra, Shikha; Kumar, Avdhesh; Panda, Bibhu Prasad
Abstract Context: Gabapentin follows saturation kinetics for absorption because of carrier-mediated transport and narrow absorption window in stomach. There is need to develop a gastroretentive formulation to maximize the absorption without crossing the saturation threshold for absorption. Objective: The aim was to develop a gastroretentive formulation of gabapentin to increase the fraction of drug absorbed in stomach. Materials and methods: Sodium alginate and sodium carboxymethylcellulose were used to formulate the microsphere by ionotropic gelation with calcium chloride. The formulation was optimized using a three-factor, three-level Box–Behnken design. Results: The particle size varied from 559.50 to 801.10 μm, entrapment efficiency from 61.29 to 81.00% and in vitro release from 69.40 to 83.70%. The optimized formulation was found using point-prediction, and formulation OF-3 showed optimum results at 608.21 μm size, 79.65% entrapment efficiency and 82.72% drug release and 81% mucoadhesion up to 10 h. The drug release was controlled for more than 12 h. Discussion: The particle size was most influenced by sodium alginate while entrapment efficiency and drug release depended upon both polymers. The release followed Higuchi model. Conclusion: Gastroretentive formulation was successfully optimized by a three-factor, three-level Box–Behnken design and found to be useful.